Kepraktisan E-Module Berbasis Project Based Learning Pada Materi Vektor - Nadiyah Mufidah; Tika Dwi Nopriyanti; Yunika Lestaria Ningsih (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
The purpose of this study is to evaluate the feasibility of vector e-modules based on project-based learning for students in class X SMA. This study is a continuation of development research using a 4D model (define, design, development, and dissemination). The feasibility of the e-module is assessed in the development section, which includes three trial stages: one-to-one, small group, and field test. 35 students from SMA Negeri 15 Palembang participated in this study. Questionnaires, interviews, and written tests were used to collect data. The results of the questionnaire and written test were analyzed quantitatively, while the data from interviews were analyzed qualitatively. Based on the results of the one-to-one stage, it is clear that the e-module has an interesting appearance, is simple to use, and includes videos to help students understand the material. The e-module has a practicality level of 77,4 % in the small-group stage and 79,4 percent in the field test stage. This data is backed up by students' ability to solve vector material problems in the e-module, which is 78.4 percent at the field test stage. Based on the data analysis results, it is possible to conclude that the e-module vector based on project-based learning is practically used in learning with a moderate level of practicality.Â Keywords: E-Module, Project Based Learning, Vector